2012
DOI: 10.1158/0008-5472.can-10-4621
|View full text |Cite
|
Sign up to set email alerts
|

GLI1 Inhibition Promotes Epithelial-to-Mesenchymal Transition in Pancreatic Cancer Cells

Abstract: The Hedgehog (HH) pathway has been identified as an important deregulated signal transduction pathway in pancreatic ductal adenocarcinoma (PDAC), a cancer type characterized by a highly metastatic phenotype. In PDAC, the canonical HH pathway activity is restricted to the stromal compartment while HH signaling in the tumor cells is reduced as a consequence of constitutive KRAS activation. Here we report that in the tumor compartment of PDAC the HH pathway effector transcription factor GLI1 regulates epithelial … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
49
2
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 62 publications
(57 citation statements)
references
References 49 publications
5
49
2
1
Order By: Relevance
“…These data suggest that different categories of TGF␤-responsive genes are regulated with or without the involvement of GLI1. We previously showed that TGF␤ could stimulate epithelial-to-mesenchymal transition via changes in gene expression in cells depleted of GLI1, consistent with the ability of TGF␤ to alter the expression of some genes via GLI1-independent mechanisms (44). Thus, our studies increase the repertoire of mechanisms utilized by the TGF␤ pathway in cancer cells by showing that GLI1 can act as a downstream mediator of TGF␤ signaling via cooperation with the SMADs for the regulation of certain genes.…”
Section: Discussionsupporting
confidence: 86%
“…These data suggest that different categories of TGF␤-responsive genes are regulated with or without the involvement of GLI1. We previously showed that TGF␤ could stimulate epithelial-to-mesenchymal transition via changes in gene expression in cells depleted of GLI1, consistent with the ability of TGF␤ to alter the expression of some genes via GLI1-independent mechanisms (44). Thus, our studies increase the repertoire of mechanisms utilized by the TGF␤ pathway in cancer cells by showing that GLI1 can act as a downstream mediator of TGF␤ signaling via cooperation with the SMADs for the regulation of certain genes.…”
Section: Discussionsupporting
confidence: 86%
“…Interestingly, patients with severe desmoplasia, a histopathological feature associated with poor prognosis, appeared to have a significantly lower median level of GLI1 expression when compared with those patients with none, mild, or moderate desmoplasia (0.48 versus 2.08 median expression, Kruskal Wallis (p ϭ 0.0238)). These results, coupled with recent reports (28,29), suggest that lower levels of GLI1 at later stages of pancreas tumorigenesis promote tumor progression. Together, these findings demonstrate that the loss of GLI1 results in increased tumor burden ultimately leading to accelerated morbidity and poor prognosis.…”
Section: Resultssupporting
confidence: 77%
“…In mice, the overexpression of Gli1 in the skin induces the formation of skin lesions and the loss of E-cadherin expression [105]. In pancreatic cancer cells, expression of E-cadherin is independent of Snail and Slug but directly regulated by Gli1 [106]. The inhibition of the Hh pathway with cyclopamine, a steroid that blocks SMO, decreases the expression of Gli1 and Gli2, but also the expression of Sip1, Snail2 and Twist2 [107].…”
Section: Hedgehog Signallingmentioning
confidence: 99%